2020
DOI: 10.1213/ane.0000000000005320
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Positions During Surgical Preparation With Combined Spinal-Epidural Anesthesia for Elective Cesarean Delivery: A Randomized Controlled Trial

Abstract: BACKGROUND: The intraoperative 15° left-tilt position during cesarean delivery has more recently been questioned regarding its effect on fetal acid-base balance and is a frequent source of complaints by surgeons. We hypothesized that a 30° left-tilt position during surgical preparation could improve the acid-base balance of the fetus compared with the 15° left-tilt or supine position during surgical preparation. METHODS: Women undergoing elective cesare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
2
8
0
1
Order By: Relevance
“…These results are in line with recent findings from randomized controlled trials investigating the lack of efficacy of the 15° left lateral tilt at reducing maternal hypotension or affecting fetal acid base status, 2 further supporting the paradigm shift to finally abandon the practice of lateral tilt in obstetric anesthesia. Nevertheless, the authors’ conclusion of recommending inferior vena cava (IVC) examinations as a potentially useful tool in detecting patients more sensitive to position is debatable.…”
supporting
confidence: 87%
“…These results are in line with recent findings from randomized controlled trials investigating the lack of efficacy of the 15° left lateral tilt at reducing maternal hypotension or affecting fetal acid base status, 2 further supporting the paradigm shift to finally abandon the practice of lateral tilt in obstetric anesthesia. Nevertheless, the authors’ conclusion of recommending inferior vena cava (IVC) examinations as a potentially useful tool in detecting patients more sensitive to position is debatable.…”
supporting
confidence: 87%
“…These authors have shown a lack of effect of a lateral tilt of 15 degrees when compared with a supine position in elective cesarean section with crystalloid coloading and phenylephrine infusion 4. Improvements of hemodynamic stability with a 30 degrees lateral tilt—as reported by Liu et al2 is in line with a recent magnetic resonance imaging study in unanesthetised volunteers, where 30 degrees left lateral tilt was most effective in reducing caval compression 5…”
Section: Commentsupporting
confidence: 63%
“…Left lateral tilt—an almost perpetual topic in obstetric anesthesia 1. The study by Liu et al2 had to be started twice, the initial plan was to maintain the assigned position (supine, 15 tilt, 30 degrees lateral tilt) during surgery. This was unacceptable for the obstetricians performing the surgery and the study was restarted with a modified protocol, where the allocated position was maintained until surgical preparation and changed to supine afterwards.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the tilt angle did not influence umbilical artery pH between the three groups, indicating that tilt angle may provide no benefit or harm to the fetus. 59 We underestimate the angle Measuring the actual table inclination, established by 16 different anaesthetists for caesarean section, demonstrated that all of them underestimated the angle. 60 Accordingly, a comparable analysis of 100 caesarean sections reported too slight a tilt by visual judgement in 75 patients 61 (Fig.…”
Section: Implications For Obstetric Anaesthesiamentioning
confidence: 96%